The effect of muscle stiffness and damping on simulated impact force peaks during running - Nigg, B. M.; Liu, W. (Journal of Biomechanics, 1999)
It has been frequently reported that vertical impact force peaks during running change only minimally when changing the midsole hardness of running shoes. However, the underlying mechanism for these experimental observations is not well understood. An athlete has various possibilities to influence external and internal forces during ground contact (e.g. landing velocity, geometrical alignment, muscle tuning, etc.). The purpose of this study was to discuss one possible strategy to influence external impact forces acting on the athlete's body during running, the strategy to change muscle activity (muscle tuning). The human body was modeled as a simplified mass-spring-damper system. The model included masses of the upper and the lower bodies with each part of the body represented by a rigid and a non-rigid wobbling mass. The influence of mechanical properties of the human body on the vertical impact force peak was examined by varying the spring constants and damping coefficients of the spring-damper units that connected the various masses. Two types of shoe soles were modeled using a non-linear force deformation model with two sets of parameters based on the force-deformation curves of pendulum impact experiments. The simulated results showed that the regulation of the mechanical coupling of rigid and wobbling masses of the human body had an influence on the magnitude of the vertical impact force, but not on its loading rate. It was possible to produce the same impact force peaks altering specific mechanical properties of the system for a soft and a hard shoe sole. This regulation can be achieved through changes of joint angles, changes in joint angular velocities and/or changes in muscle activation levels in the lower extremity. Therefore, it has been concluded that changes in muscle activity (muscle tuning) can be used as a possible strategy to affect vertical impact force peaks during running.